Impact of aerobic versus resisted exercise training on systemic inflammation biomarkers and quality of Life among obese post-menopausal women - Abd El-Kader, Shehab M (Afr Health Sci, 2019)
BACKGROUND: Although post-menopausal obesity is an important public national health problem in Saudi Arabia, to date no study has evaluated the effects of weight reduction on biochemical & clinical parameters and quality of Life for obese Saudi post-menopausal women. OBJECTIVE: The aim of this study was examine the effects of aerobic versus resisted exercise training effects upon systemic inflammation biomarkers and quality of life for obese post-menopausal Saudi women. MATERIAL AND METHODS: One hundred Saudi post-menopausal obese women participated in this study, their age ranged from 50–58 years and their body mass index (BMI) ranged from 30–35 kg/m2. All participants were divided into two equal groups: The first group received aerobic exercise training on treadmill where, the second group received resisted exercise training. Health-related quality of life (SF-36 HRQL), tumor necrosis factor- alpha(TNF-α), Interleukin-2(IL-2), Interleukin-4 (IL-4), Interleukin-6 (IL-6) and C-reactive protein (CRP) were measured before and after 3 months at the end of the study. RESULTS: The mean values of SF-36 HRQL subscale scores were significantly increased, while the mean value of TNF-α, Il-2, IL-4, IL-6, CRP and BMI were significantly decreased in both groups after treatments. There were significant differences between mean levels of the investigated parameters in group (A) and group (B) after treatment with more changes in patients received aerobic exercise training. CONCLUSION: The current study provides evidence that aerobic exercise is more appropriate than resisted exercise training in modulating inflammatory cytokines and quality of life among obese post-menopausal women.